Pengaruh Kepemilikan Institusional, Komite Audit, Solvabilitas, Dan Ukuran Perusahaan Terhadap Manajemen Laba - Akmal Hidayat; Endang Kurniati; Iratika Tambunan; Ilham Hidayah Napitupulu (P3M Politeknik Negeri Bengkalis, 2025)
The focus of this study is to examine the effect of institutional ownership, audit committee, solvency, and company size on earnings management. Earnings management is an effort by company managers to influence financial statement information that aims to deceive stakeholders who want to know the company's performance. This study was tested on 140 data from 20 consumer goods sector companies listed on the Indonesia Stock Exchange in 2016-2022 which were selected using the purposive sampling method. The analysis technique used is multiple linear regression analysis. The results of this study indicate that company size has an effect on earnings management while institutional ownership, audit committee, and solvency do not have an effect on earnings management.